(untitled) (Scientific journal of the Fergana State University, 2025)
The article analyzes economic factors that influence the settlement of the population in the region. It is argued that economic factors are the most influential in determining the location in a modern market economy. Also, each of the economic factors (the level of development of industry and industrialization, the development of agriculture and rural population, transport infrastructure and landscaping, employment and the state of the labor market, housing prices and housing policy) was considered separately.